A review of all-solid-state electrolytes for lithium batteries: high-voltage cathode materials, solid-state electrolytes and electrode–electrolyte interfaces. (15th February 2023) - Ma, Mingming; Zhang, Menghui; Jiang, Bitao; Du, Yang; Hu, Bingcheng; Sun, Chengguo
Abstract : Solid-state electrolytes attract great attention due to their advantages in safety, electrochemical stability and battery packaging. High-voltage cathode materials and the Li metal anode further increase the energy density and electrochemical cycling properties. Abstract : Solid-state electrolytes (SEs) have attracted great attention due to their advantages in safety, electrochemical stability and battery packaging; especially, they can match with high-voltage cathode materials and the Li metal anode to further increase the energy density and electrochemical cycling property. In the past decade, great breakthroughs have been made in the research of electrodes, electrolyte materials and electrode/electrolyte interfaces of high-voltage all-solid-state lithium batteries (ASSLBs). Herein, we summarize the emerging high-voltage cathode materials and their matched solid-state electrolytes; we also analyze the interface problem from a new perspective (corrosion). The authors provide their perspectives on the state of current ASSLBs research, and aim to propose possible research directions for the development of high-voltage ASSLBs in the future.